Beyond the grave [compact disc, unabridged] - Watson, Jude (39 clues, 2009)
A clue found in Book 3 sends Amy and Dan jetting off to find out what's behind the fierce rivalry between the Tomas and Ekaterina branches of the Cahill family. Was a clue stolen from the Tomas branch? Where is it now? And, most important, can Amy and Dan get their hands on it before their rivals do?